On the Asymptotic Expansions of the (p,k)-Analogues of the Gamma Function and Associated Functions - Tomislav Burić (Axioms)
General asymptotic expansion of the <semantics>(p,k)</semantics>-gamma function is obtained and various approaches to this expansion are studied. The numerical precision of the derived asymptotic formulas is shown and compared. Results are applied to the analogues of digamma and polygamma functions, and asymptotic expansion of the quotient of two <semantics>(p,k)</semantics>-gamma functions is also derived and analyzed. Various examples and application to the k-Pochhammer symbol are presented.